2021
DOI: 10.5194/tc-2021-210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wave dispersion and dissipation in landfast ice: comparison of observations against models

Abstract: Abstract. Observations of wave dissipation and dispersion in sea ice are a necessity for the development and validation of wave-ice interaction models. As the composition of the ice layer can be extremely complex, most models treat the ice layer as a continuum with effective, rather than independently measurable, properties. While this provides opportunities to fit the model to observations, it also obscures our understanding of the wave-ice interactive processes, particularly, it hinders our ability to identi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Voermans et al . [57] compared several viscoelastic and basal friction models with data obtained in landfast ice. It was found that for short waves viscoelastic effects dominated and for long waves basal friction dominated.…”
Section: Applications Of Theories and Resulting Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Voermans et al . [57] compared several viscoelastic and basal friction models with data obtained in landfast ice. It was found that for short waves viscoelastic effects dominated and for long waves basal friction dominated.…”
Section: Applications Of Theories and Resulting Findingsmentioning
confidence: 99%
“…Many of these studies focused on pancake ice or broken ice fields [5255]. A few also investigated grease ice [56] and landfast ice [57]. Most of these studies addressed wave attenuation, with a few included wave speed [51,5759].…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A conservative range for Y and σ was chosen to describe the full range of sea ice material properties, with σ ∈[0.1, 0.7] MPa and Y ∈[0.2, 9] GPa (Karulina et al., 2019; Timco & Weeks, 2010). The range for the attenuation reduction coefficient for broken ice is β ∈[0.01, 0.1] (Voermans et al., 2021). Here, we choose β = 0.05 as being the median value.…”
Section: Methodsmentioning
confidence: 99%
“…Both report two distinct phases in attenuation of waves by sea ice: strong attenuation under unbroken ice conditions, and unimpeded propagation under broken ice conditions. Wave attenuation reduces by at least an order of magnitude once the ice is broken (Voermans et al., 2021), hence the waves can propagate further and break more sea ice.…”
Section: Introductionmentioning
confidence: 99%